2012
DOI: 10.1111/j.1747-0285.2012.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Acyl Coenzyme A: Cholesterol Acyltransferase Inhibitors: Pharmacophore‐Based Virtual Screening, Synthesis and Pharmacology

Abstract: The present study describes ligand-based pharmacophore modeling of a series of structurally diverse acyl coenzyme A cholesterol acyltransferase inhibitors. Quantitative pharmacophore models were generated using HypoGen module of Discovery Studio 2.1, whereby the best pharmacophore model possessing two hydrophobic, one ring aromatic, and one hydrogen bond acceptor feature for inhibition of acyl coenzyme A cholesterol acyltransferase showed a very good correlation coefficient (r = 0.942) along with satisfactory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…We used Discovery Studio 4.0 (DS) for the pharmacophore model generation and virtual screening followed by molecular docking study. DS is a commercial software package consisting of several modules and widely used for pharmacoinformatics studies . In DS, 3D QSAR pharmacophore generation module was used in which a set of DNA GyrB inhibitors and activity data were taken as input to create potential hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…We used Discovery Studio 4.0 (DS) for the pharmacophore model generation and virtual screening followed by molecular docking study. DS is a commercial software package consisting of several modules and widely used for pharmacoinformatics studies . In DS, 3D QSAR pharmacophore generation module was used in which a set of DNA GyrB inhibitors and activity data were taken as input to create potential hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…The DS is commercially available software containing several module packages and widely used in the pharmacoinformatics drug discovery [35][36][37][38]. The 3D QSAR Pharmacophore Generation module enables the use of structure and activity data for a set of potential HIV-protease ligand to create hypotheses.…”
Section: Methodsmentioning
confidence: 99%
“…By analyzing the published ACAT pharmacophore [43,44], we found that subtype selectivity was not considered fully. For instance, the ACAT pharmacophore without selectivity was constructed in Mahesh's paper [43], which had only four features.…”
Section: Validation Of the Pharmacophore Modelmentioning
confidence: 99%
“…By analyzing the published ACAT pharmacophore [43,44], we found that subtype selectivity was not considered fully. For instance, the ACAT pharmacophore without selectivity was constructed in Mahesh's paper [43], which had only four features. While in this paper, both ACAT-1 and ACAT-2 pharmacophores with selectivity had seven features, which showed more features could improve the specificity and selectivity of pharmacophore [44] had constructed the pharmacophore models of ACAT-1 and ACAT-2 inhibitors, respectively.…”
Section: Validation Of the Pharmacophore Modelmentioning
confidence: 99%